Lobectomy of Single Pulmonary Nodul Increased Quality of Life and Lung Function in 1 and 3 month After Surgery - Susanti, Lia; Djajalaksana, Susanthy; Indah Sari, Fitri; Rachma Erawati, Dini; Setyo Yudhanto, Hendy; Kusuma Wardhana, Koernia (Universitaas Brawijaya, 2025)
Introduction: Since a single pulmonary nodule (SPN) usually doesn't cause any respiratory symptoms, it is frequently found by accident. On a chest X-ray, the incidence of SPN is 0.1-0.2%, and on a contrast-enhanced CT scan of the thorax, it is 13%. In populations at high risk, the incidence rises to 9–33%. Contrast-enhanced CT scans are essential for early detection in order to assess and choose a course of treatment. About 40–50% of SPNs are malignant, with adenocarcinoma being the most prevalent subtype, making for 47% of all instances of lung cancer. Surgical intervention is advised in the early stages. Case Report: A 62-year-old nonsmoker arrived with haemoptysis and a persistent cough. A contrast-enhanced CT scan revealed a solid lesion of 2.8 cm x 2.7 cm x 2.4 cm, classified as stage IA. A chest X-ray revealed a tiny mass measuring 1.5 cm x 1 cm. Following a lobectomy, the patient's pathology revealed Non-Small Cell Lung Carcinoma (NSCLC), specifically adenocarcinoma. To rule out organ metastases, immunohistochemistry (IHC) assays were used. Conclusion: Lobectomy for SPN adenocarcinoma stage IA improves lung function and quality of life at one and three months post-surgery.